2015
DOI: 10.1016/j.drugalcdep.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and repeated dosing of the synthetic cannabinoid CP55,940 on intracranial self-stimulation in mice

Abstract: Background Synthetic cannabinoids have emerged as a significant public health concern. To increase the knowledge of how these molecules interact on brain reward processes, we investigated the effects of CP55,940, a high efficacy synthetic CB1 receptor agonist, in a frequency-rate intracranial self-stimulation (ICSS) procedure. Methods The impact of acute and repeated administration (seven days) of CP55,940 on operant responding for electrical brain stimulation of the medial forebrain bundle was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
4
9
0
Order By: Relevance
“…The current study showed that CP55940 produced dose-dependent depression of ICSS in rats. Similar results have been previously reported in mice and rats [44,45]. In addition, other CB1 agonists produced similar effects in ICSS such as Δ9-tetrahydrocannabinol and WIN55,212-2 ((R)-(+)-[2,3-Dihydro-5-methyl-3-(4-morpholinylmethyl)pyrrolo[1,2,3-de]-1,4-benzoxazin-6-yl]-1-naphthalenylmethanone mesylate) [31,46].…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that CP55940 produced dose-dependent depression of ICSS in rats. Similar results have been previously reported in mice and rats [44,45]. In addition, other CB1 agonists produced similar effects in ICSS such as Δ9-tetrahydrocannabinol and WIN55,212-2 ((R)-(+)-[2,3-Dihydro-5-methyl-3-(4-morpholinylmethyl)pyrrolo[1,2,3-de]-1,4-benzoxazin-6-yl]-1-naphthalenylmethanone mesylate) [31,46].…”
Section: Discussionsupporting
confidence: 92%
“…with mu opioid receptor agonists like morphine (Legakis and Negus 2018;Miller et al 2015a;Reid 1987;Wiebelhaus et al 2016) or high nicotine doses (Freitas et al 2016)], (2) tolerance to ICSS depression without emergence of ICSS facilitation [e.g. with cannabinoid receptor agonists like Δ9-tetrahydrocannabinol (Grim et al 2015;Kwilasz and Negus 2012), the N-methyl-Daspartate glutamate receptor antagonist ketamine (Hillhouse et al 2014), and the delta opioid receptor agonist SNC80 (Negus et al 2012)], or (3) sustained ICSS depression [e.g. with the kappa agonist salvinorin A (Potter et al 2011), the dopamine D2 agonist quinpirole (Negus et al 2012), and the serotonin 5HT1A/2A receptor agonist flibanserin (Lazenka et al 2016)].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in developing tolerance to depression of ICSS after repeated exposure to cannabinoids have been reported. Tolerance is completely developed after repeated exposure to Δ 9 -THC (Kwilasz and Negus, 2012 ) but partially developed after CP55940 (Grim et al, 2015 ), and not developed after WIN55212-2 administration (Mavrikaki et al, 2010 ), suggesting that the different affinity of Δ 9 -THC vs. SC for the CB1 receptors could play a role in developing this tolerance (Grim et al, 2015 ).…”
Section: Synthetic Marijuana and The Cannabimimeticsmentioning
confidence: 99%